Electrochemical performance of novel NGCO-LSCF composite cathode for intermediate temperature solid oxide fuel cells. (21st August 2020) - Samreen, Ayesha; Galvez-Sanchez, Maria; Steinberger-Wilckens, Robert; Arifin, Nor Anisa; Saher, Saim; Ali, Shahid; Qamar, Affaq
Abstract: In this study, a co-dopant CGO was synthesized to produce more efficient cathode materials for intermediate temperature solid oxide fuel cell (IT-SOFC) applications. Neodymium (Nd) was doped into CGO in four different weight ratios in the formula Ndx Gd0.15 Ce0.85- x O2-δ (NGCO); the selected percentages for x were 1%, 3%, 5% and 7%. XRD patterns showed pure phase for all synthesized compositions and good compatibility at high temperature under static air with the most common ceramic cathode material in IT-SOFC (La0·60 Sr0·40 Co0·20 Fe0·80 O2-ä, LSCF). Impedance spectroscopic characterization of symmetrical cells of the composite NGCO-LSCF at different temperatures (650–800 °C in steps of 50 °C) and a frequency range of 0.1–1 MHz in synthetic air revealed interesting results. The lowest polarization resistance (Rp ) was achieved for Nd0.05 Gd0.15 Ce0·80 O2-δ (0.06 Ω cm 2 at 800 °C, 0.17 Ω cm 2 at 750 °C, 0.31 Ω cm 2 at 700 °C, and 0.59 Ω cm 2 at 650 °C). The expected decrease in Rp was not observed for the sample with higher Nd content (7% Nd). Thus, it can be said that there is a distinction between the compositions Nd0.05 Gd0.15 Ce0·80 O2-δ and Nd0.07 Gd0.15 Ce0·78 O2-δ ; the co-doping of Nd in NGCO incremented the oxygen ion diffusion path, thereby optimization in the triple phase boundary (TPB) sites was obtained. Furthermore, SEM and TGA measurements were conducted to clarify the reasons of such improvements. This work showed that an NGCO-LSCF composite can be considered as a potential candidate for cathode material for future IT-SOFC applications. Highlights: Ndx co-doped with Gd0.15 Ce0.85- x O2-δ (GCO) by varying the weight ratio of Nd and Ce. EIS measurement was conducted on the NGCO-LSCF composite. Lowest polarization resistance, Rp, was achieved for Nd 0.05 Gd0.15 Ce0·80 O2-δ . SEM and TGA measurements clarify the reason for the lower value of Rp .